Association Between Claudin-5 And Angulin-1 In Alzheimer's Disease - Nawal Abdullah Murtadha (Academia Open, 2025)
General Background: Alzheimer’s disease is a progressive neurodegenerative disorder in which cognitive decline is closely linked to blood–brain barrier dysfunction. Specific Background: Tight-junction proteins such as Claudin-5 and Angulin-1 play key roles in maintaining barrier integrity, yet their involvement in Alzheimer’s pathology remains insufficiently clarified, and evidence on associated micronutrient alterations is still limited. Knowledge Gap: Despite emerging data suggesting barrier disruption and B-vitamin deficiencies in Alzheimer’s disease, the combined diagnostic relevance of Claudin-5, Angulin-1, and vitamins B9 and B12 has not been systematically examined. Aims: This study investigates the relationship between Claudin-5 and Angulin-1 in Alzheimer’s disease and evaluates differences in serum vitamin B9 and B12 levels between affected individuals and healthy controls. Results: Serum analyses revealed significantly reduced Angulin-1, Claudin-5, vitamin B9, and vitamin B12 levels in Alzheimer’s patients, alongside marked alterations in lipid profiles. ROC analysis demonstrated exceptionally high diagnostic performance for all measured biomarkers. Novelty: This work provides integrated biochemical evidence linking tight-junction protein depletion with B-vitamin deficiencies in Alzheimer’s disease, suggesting a coordinated disruption of vascular and metabolic pathways. Implications: The identified biomarkers show strong potential for non-invasive diagnostic applications and may guide the development of therapeutic strategies aimed at restoring barrier integrity and micronutrient balance.Highlight : Claudin-5 and Angulin-1 show significant reductions in Alzheimer’s patients, reflecting impaired tight-junction function in the blood–brain barrier. Vitamin B9 and B12 levels are markedly lower in Alzheimer’s patients than in healthy controls, indicating an important metabolic alteration. All biomarkers demonstrate high diagnostic performance, with strong sensitivity and specificity based on ROC analysis. Keywords : Claudin-5, Angulin-1, Alzheimer’s disease, Vitamin B9, Vitamin B12